A framework for leading school change in using ICT: Measuring Change - Trinidad, Sue; Newhouse, P.; Clarkson, B. (AARE Inc., 2005)
Over the last three decades many models explain the processes involved in the adoption and use of ICT in education. Based on this literature, a three-tiered framework and associated instruments were developed to use with Western Australian teachers to measure and support change in using ICT. This framework can be used to support, describe and promote good practice in the use of ICT in learning and teaching in schools and is multi-faceted and flexible enough to be used by individuals, groups, schools or educational organizations. The aims and purposes of the framework were to describe quality pedagogy in the use of ICT to effectively support student learning in schools; to assist teachers in planning to integrate ICT into learning environments; to describe progress by teachers as they move towards the integration of ICT in quality pedagogy; to assist teachers in the development of their own practice in the use of ICT to support student learning; and to provide a tool for teacher dialogue for ICT integration with good pedagogy and provide topics or questions that describe concerns teachers may have. This framework was based on a review of the literature on the progression of teachers in their integration of ICT in learning and teaching processes. It was positioned within a broader framework for the implementation of ICT in schools to connect with students, learning environments, school and system organizations. This paper describes the process and results from this research undertaken to develop the framework for schools and teachers.